THE EFFECT OF MADRASAH HEAD LEADERSHIP, ACADEMIC SUPERVISION AND FUNCTIONAL TRAINING ON TEACHER PERFORMANCE ALIYAH MADRASAH INTHE DISTRICT OF BARRU - ABDUL GANI; Basri Modding; Andi Bunyamin; Akhmad Syahid (Universitas Cokroaminoto Palopo, 2021)
This research was conducted with the aim to; (1) examine and analyze the influence of Madrasah head leadership, academic supervision, and functional training on the performance of Madrasah Aliyah teachers (2) examine and analyze the influence of Madrasah head leadership on the performance of Madrasa Aliyah teachers (3) examine and analyze the effect of Madrasah head supervision on the performance of Mardasar Aliyah teachers (4) examine and analyze the effect of functional training on the performance of Madrasah Aliyah teachers in kabupaten Barru, and This research uses primary data and secondary data, primary data through a survey on Madrasah Aliyah in kabupaten Barru which was conducted from September to November 2020 with a population of 273 teachers from 12 Madrasah Aliyah. Determination of the sample using the slovin formula, which is 12 Madrasah Aliyah and 162 respondents were selected. Secondary data includes document data in Madrasah resulting from teacher performance assessments conducted by the head of Madrasah each year. The data analysis used is descriptive to explain and describe the research data, while the quantitative data analysis uses Multiple Linear Regression analysis tool with SPSS program. The results of this research, there are value (R2/r-square) of 0.976. Means that 97.6 percent of the independent variables are madrasah principal leadership, academic supervision, and functional training simultaneously affect the dependent variable on the performance of madrasah aliyah teachers and the rest is about 2.4% affect the other variables that are not included in this research. And variably, the leadership of the madrasah principal has a positive and significant effect on the performance of madrasah aliyah teachers in Barru by 96.9 percent, while the other 13.1 percent can be explained by other factors not examined in this research, and academic supervision has an effect positive and significant impact on teacher performance at madrasah aliyah in Barru. by 89.1 percent, while the other 10.9 percent can be explained by other factors, as well as, functional training has a significant effect on the performance of madrasah aliyah teachers in Barru by 72.1 percent, while the other 27.9 percent can be explained by other factors, and subsequently the leadership of the head of the state madrasah aliyah, and the implementation of academic supervision and functional training is better than private madrasah aliyah in Barru.